Radical cystectomy with a Y-shaped orthotopic ileal neobladder, early uretero-neobladder anastomosis outcomes at Khon Kaen Hospital - Somwung, Theerayuth (Insight Urology, 2022)
Objective: To evaluate the clinical complications and functional outcomes associated with the modified Y-pouch neobladder technique, in particularly those related to the prevention of anastomosis stricture. Materials and Methods: Functional outcomes and associated complications were evaluated in 25 patients (23 men, 2 women) who underwent radical cystectomy with Y-pouch neobladder by isolating 50 cm of the ileum between October 2010 and December 2020. Clinical complications included anastomosis stricture formation, hydronephrosis, pyelonephritis, vesical stone formation, and renal deterioration. Results: No cases exhibited uretero-neobladder anastomosis stricture, urethro-neobladder anastomosis stricture, or vesical stones. In addition, no complications were observed in relation to metabolic acidosis. One year after surgery, daytime and nighttime continence rates among patients were 88% and 72%, respectively, with almost every case exhibiting near-normal voiding frequency. The average maximal neobladder capacity was 425.60±20.83 ml with a mean follow-up period of 2.8 years. There was a no statistically significant increase in creatinine with values of 1.45 mg/dl, 1.14 mg/dl, 1.21 mg/dl, and 1.35 ml/dl being recorded at preoperative baseline, 3, 6 and 12 months, respectively. Conclusions: The Y-pouch neobladder created by isolating 50 cm of the ileum showed a low incidence of uretero-neobladder anastomosis and urethra-anastomosis stricture rate. In addition it was a straightforward procedure with a quickly reconstructed reservoir, had good functional outcomes which were comparable to most popular orthotopic neobladders, had no significant increase in postoperative creatinine levels and improved quality of life for patients.